Estudio de prefactibilidad para la instalación de una planta productora de losetas en base a caucho reciclado - Aparicio Cotrina, Jorge Luis (2022)
This research work will expose the prefeasibility study for the implementation of a tile production plant based on recycled rubber, in the same way the economic, technical, environmental, and financial viability of the project will be evaluated. Currently, the disuse of tires at the end of their useful life means that the vast majority do not have an adequate final disposal. This presents a major problem for the country. Also, the use of products made from recycled tires is not being exploited. For this reason, the project seeks to supply the market with a unique product that will satisfy the demand for coatings, in this case rubber tiles. The layout of the project is made up of eight chapters, beginning with the explanation of the problem and the idea of how to solve it, the justification of the project and the objectives. Then, the demand for the project was determined by analyzing the market and 443,612 units were obtained for the first year. Next, the location of the plant was calculated using the macro and micro location factors, leaving the department of Lima and the district of San Juan de Lurigancho as optimal. Likewise, a plant size of 3,348,084 kg was obtained, which allowed satisfying the demand found. Subsequently, an analysis of the installed capacity was carried out and the operation known as the bottleneck was identified, this being the mixing activity that indicated a capacity of 3,359,070 kilograms per year. Next, the organizational structure of the company was determined. After that, the economic and financial evaluation of the project was carried out and a VNA of 896,957 soles was obtained as a result, indicating that the project is profitable, a TIR of 40%, which is greater than the COK (10.21%), a B/C of 2.62 soles and a RP of approximately 3 years and 5 months. The project, in financial and economic terms, is profitable. Finally, the results of the social indicators of the project were interpreted and it was determined that the relationship between the investment and the impact that starting the project would generate is positive.